MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF ISLAM - Muhamad Asror; Irpan Syah; Ahmad Roisuddin (STAI Darussalam Lampung, 2024)
The purpose of this article is to discuss the management of education from an Islamic perspective, the research is library research, with the method of collecting data documentation. The analysis uses content analysis. The results of the study state that Islamic education management as a family of science certainly has specific characteristics regarding what (ontology), how (epsitemology), and for what (axiology) management knowledge respectively. Islamic education management is a process of structuring or managing Islamic education institutions involving Muslim human resources and mobilising them to achieve Islamic education goals effectively and efficiently. Islamic education management has two objects, namely material objects and formal objects. The material objects of Islamic education management science include the scriptures, the products of human reason, and the physical world. The ontological foundation of education management regulates all educational activities, namely, planning, organising, mobilising (motivation, leadership, decision-making, communication, coordination, and negotiation as well as organisational development) and controlling (including monitoring, assessment, and reporting). The epistemological basis is needed in educational management or educational science experts in order to develop their knowledge productively and responsibly. The principles of Islamic education management are the principle of amar ma'ruf nahi munkar, the principle of upholding the truth, the principle of upholding justice, and the obligation to deliver a good message.